Selection of tool diameter by New Caledonian crows Corvus moneduloides. - Chappell, J; Kacelnik, A (2004)
One important element of complex and flexible tool use, particularly where tool manufacture is involved, is the ability to select or manufacture appropriate tools anticipating the needs of any given task-an ability that has been rarely tested in non-primates. We examine aspects of this ability in New Caledonian crows-a species known to be extraordinary tool users and manufacturers. In a 2002 study, Chappell and Kacelnik showed that these crows were able to select a tool of the appropriate length for a task among a set of different lengths, and in 2002, Weir, Chappell and Kacelnik showed that New Caledonian crows were able to shape unfamiliar materials to create a usable tool for a specific task. Here we examine their handling of tool diameter. In experiment 1, we show that when facing three loose sticks that were usable as tools, they preferred the thinnest one. When the three sticks were presented so that one was loose and the other two in a bundle, they only disassembled the bundle when their preferred tool was tied. In experiment 2, we show that they manufacture, and modify during use, a tool of a suitable diameter from a tree branch, according to the diameter of the hole through which the tool will have to be inserted. These results add to the developing picture of New Caledonian crows as sophisticated tool users and manufacturers, having an advanced level of folk physics.